Resistance training using different elastic components offers similar gains on muscle strength to weight machine equipment in Individuals with COPD: A randomized controlled trial - Coelho Figueira Freire, Ana Paula [UNESP]; Marcal Camillo, Carlos Augusto; Alencar Silva, Bruna Spolador de [UNESP]; Uzeloto, Juliana Souza [UNESP]; Lima, Fabiano Francisco de [UNESP]; Gobbo, Luis Alberto [UNESP]; Ramos, Dionei [UNESP]; Cipulo Ramos, Ercy Mara [UNESP] (Taylor & Francis Inc, 2020)
Purpose: To compare the effects of three modalities of resistance training, two using elastic components and one using conventional weight machine on peripheral muscle strength in Individuals with chronic obstructive pulmonary disease (COPD). Effects on exercise capacity, impact of disease on health status, body composition and daily level of physical activity were investigated as secondary endpoints. Methods: Forty-eight participants were randomly allocated (Trials Registry #RBR-6V9SJJ) into Elastic band group (Theraband (R)) (EBG), Elastic tubes training using Lemgruber (R) (ETG), and Conventional training with weight machine equipment (CG). Participants were evaluated before and after 12 weeks of training regarding peripheral muscle strength by dynamometry; impact of disease on health status via COPD Assessment Test, CAT; exercise capacity by 6-min walk test, 6MWT; body composition by bioelectrical impedance; and daily level of physical activities via accelerometry. Results: Inter-group comparison of training effects did not elucidate significant differences between the modalities in muscle strength (p >= .2). Likewise, all training modalities showed similar effects on CAT, body composition and daily physical activity variables with no statistical significance observed (p >= .15). Conclusions: Modalities of resistance training using elastic components presented similar effects on muscle strength, health status, exercise capacity, body composition and daily level of physical activity in individuals with COPD. The effects of elastic resistance were similar to conventional resistance training.
Keywords: Exercise; pulmonary rehabilitation; resistance training; pulmonary disease; chronic Obstructive